Review of Photini Danou's "Προδότες της Βασίλισσας και του Ἐθνους". Καθολικισμός και λόγος περί προδοσίας στην ελισαβετιανή προπαγάνδα (1558-1585) ['Traitors to the queen and the nation': Catholicism and discourse about treason in Elizabethan propaganda, 1558-1585] - Kasdagli, Aglaia E. (Historein, 2014)
Photini Danou, «Προδότες της Βασίλισσας και του Ἐθνους». Καθολικισμός και λόγος περί προδοσίας στην ελισαβετιανή προπαγάνδα (1558-1585) ['Traitors to the queen and the nation': Catholicism and discourse about treason in Elizabethan propaganda, 1558-1585], Athens 2013: Herodotos, 518 pp.